2021
DOI: 10.16920/jeet/2021/v34i0/157188
|View full text |Cite
|
Sign up to set email alerts
|

Developing Logic Building, Problem Solving, and Debugging Programming Skills Among Students

Abstract: Computer programming course has become integral part of first year curriculum in all engineering disciplines. The effectiveness in delivery of this Course largely impacts on student's curiosity in the field of programming and software development. Many students lose their interest in the coding at very early stage of their professional career if this Course is not taught effectively. The proposed work aims to improve academic delivery of the computer programming course. This work identifies loopholes in existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Additionally, sufficient training must be provided to teachers who teach lower secondary students on the fundamentals of CT so they can effectively express this idea. Students will lose interest in coding in their potential professional careers if this subject is not taught successfully (Thorat & Kshirsagar, 2021). When studying CT skills, students must have an established basis in problem-solving skills before they can create basic programme code.…”
Section: Suggestions For Improvement On the Issuesmentioning
confidence: 99%
“…Additionally, sufficient training must be provided to teachers who teach lower secondary students on the fundamentals of CT so they can effectively express this idea. Students will lose interest in coding in their potential professional careers if this subject is not taught successfully (Thorat & Kshirsagar, 2021). When studying CT skills, students must have an established basis in problem-solving skills before they can create basic programme code.…”
Section: Suggestions For Improvement On the Issuesmentioning
confidence: 99%
“…This problem is solved by different activities like assignment of small activities to handle the computer, topic-wise short code challenges, writing algorithm and drawing flowchart, and code debugging. They observed that the result and overall performance of students get improved due to such kind of active learning technique [11]. Reddy, P. C. ( 2015), analyzed that making use of software tools to see the intermediate values of a variable during program execution as well as incremental programming approach helps to improve the programming ability of students [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teaching programming courses has a lot of challenges, especially for first-year C programming courses. The first engineering students come from different backgrounds, some of them are having a problem with communication skills, less confidence, unfamiliar with friends, having traditional learning experience using paper -pen, less exposure to computer skills, and having just remembering skills rather than applying skill [10] [11]. At the first-year level, some students are having anxiety about Computer Systems [11].…”
Section: Challenges While Teaching Programming Coursesmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many different systems developed to help experts make decisions based on their opinions or preferences [2][3][4]. In any case, systems can fail, and there can be errors, called logical errors, which do not affect the functioning of the system but do affect the final result [5], and that may have enormous negative repercussions in financial terms because the systems are supposed to provide good support to decision makers.…”
Section: Introductionmentioning
confidence: 99%